2017
DOI: 10.1080/19425120.2017.1381207
|View full text |Cite
|
Sign up to set email alerts
|

Low Apparent Survival and Heterogeneous Movement Patterns of Invasive Blue Catfish in a Coastal River

Abstract: Blue Catfish Ictalurus furcatus were purposefully introduced into freshwater tributaries to Chesapeake Bay in the past, and populations have subsequently spread to new areas, negatively impacting native communities and causing concern for resource managers. To aid development of management strategies, we implemented a multiyear (2012)(2013)(2014)(2015) tagging study of invasive Blue Catfish in a 40-km stretch of the Potomac River to estimate survival and assess movement patterns. Blue Catfish (N = 1,237) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…With a sustained swimming speed of 30 cm s -1 [51], in 72 hours a 250 mm blue catfish would be able to move 77.8 km, which is greater than the maximum width of Chesapeake Bay (48 km). A mark-recapture study on blue catfish in the Potomac River in the Chesapeake Bay has shown that blue catfish are capable of such long-distance movements [52]. Telemetry tracking of this species using acoustic tags equipped with depth sensors is needed to elucidate the effects of seasonal distribution and vertical stratification in salinity on size-specific habitat use and dispersal of blue catfish.…”
Section: Discussionmentioning
confidence: 99%
“…With a sustained swimming speed of 30 cm s -1 [51], in 72 hours a 250 mm blue catfish would be able to move 77.8 km, which is greater than the maximum width of Chesapeake Bay (48 km). A mark-recapture study on blue catfish in the Potomac River in the Chesapeake Bay has shown that blue catfish are capable of such long-distance movements [52]. Telemetry tracking of this species using acoustic tags equipped with depth sensors is needed to elucidate the effects of seasonal distribution and vertical stratification in salinity on size-specific habitat use and dispersal of blue catfish.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the average minimum distance moved by Blue Catfish in the Potomac River is 24.1 km, and is not related to fish size (30.0 to 116.5 cm total length; Tuckey et al 2017). Furthermore, the entire Potomac River is used by Blue Catfish (Tuckey et al 2017), yet consumption advisories vary depending on capture location within this river. Advisories based on fish size also warrant reconsideration.…”
Section: Accepted Articlementioning
confidence: 99%
“…For example, the average minimum distance moved by Blue Catfish in the Potomac River was 24.1 km and was not related to fish size (30.0–116.5 cm TL; Tuckey et al. 2017). Furthermore, the entire Potomac River is used by Blue Catfish (Tuckey et al.…”
Section: Challenges and Opportunities In Managing A Conflict Speciesmentioning
confidence: 99%
“…An understanding of urban rat ecology is the cornerstone of any attempt to understand rats and rat-associated issues. To gain this knowledge, ecological methods such as Capture-Mark-Recapture (CMR) can be used to estimate population characteristics like abundance and density (Wilson et al, 2007;Robinson et al, 2009;Sarmento et al, 2010), demographic characteristics (Votier et al, 2005;Lachish et al, 2007;Graham et al, 2013), and movement patterns (Beirinckx et al, 2006;Lagrange et al, 2014;Tuckey et al, 2017). However, traditional CMR techniques generally assume that all individuals are equally trappable over time (Krebs and Boonstra, 1984;Conroy and Carroll, 2009;Lindberg, 2012), an assumption which has not held in other species (e.g., Byrne et al, 2012;Carter et al, 2012;Camacho et al, 2017).…”
Section: Introductionmentioning
confidence: 99%